"Back on Track": A Longitudinal Mixed Methods Study on the Rehabilitation of Young Adult Cancer Survivors. (July 2019) - Hauken, May Aasebø; Larsen, Torill Marie Bogsnes; Holsen, Ingrid
To address the multidimensional challenges faced by young adult cancer survivors, 20 young adult cancer survivors participated in a rehabilitation program. Mixed methods, including a longitudinal convergent parallel design, were employed to evaluate both process and outcome issues. Data were collected simultaneously via questionnaires, physical testing, and interviews at four separate time points. The results portrayed rehabilitation as a process involving the gradual improvement in quality of life, participation, and physical capacity, whereby finding a balance between the different aspects of life, novel insights, and multidimensional follow-ups were important factors. This study contributes to mixed methods literature as an example of how a longitudinal mixed methods approach may yield an enriched understanding of both the rehabilitation process and outcomes in cancer rehabilitation.